Research Progresses on Nutritional Components and Authenticity Identification of Camel Milk - LI Danlei, KONG Xiabing, YU Yue, HU Qian, ZHANG Jiukai, CHEN Ying (Shipin Kexue, 2025)
Camel milk is one of the important specialty dairy sources in northwest China, and rich in various nutrients including proteins, unsaturated fatty acids, amino acids, vitamins, and minerals, which exhibits remarkable antioxidant, anti-inflammatory, antibacterial and immunomodulatory activities. The nutrient composition of camel milk is affected by various factors, nutrient contents varying significantly under different conditions. Due to its rarity and unique nutrient composition, camel milk is more expensive than cow’s milk. Economically motivated camel milk adulteration has frequently occurred in the market. This review article examines the effects of species, varieties, breeds, production region, season, feeding conditions, lactation stages, and processing conditions on the nutrient composition of camel milk using omics techniques such as proteomics, metabolomics and lipidomics, and it discusses recent advancements in camel milk authenticity identification based on its characteristic components, aiming to provide theoretical guidance for the development and high-value utilization of camel milk’s nutrients and, more broadly, for the healthy development of the camel milk industry.